RELATIVE GROWTH OF THE SPECKLED SWIMMING CRAB ARENAEUS-CRIBRARIUS (LAMARCK, 1818) (BRACHYURA, PORTUNIDAE), NEAR UBATUBA, STATE OF SAO-PAULO, BRAZIL - Pinheiro, MAA; Fransozo, A. (E J Brill, 1993)
Arenaeus cribrarius is a mainly tropical crab that occurs in the Western Atlantic Ocean, Brazil being its type-locality. The species ranges from Vinevard Sound, Massachusetts, USA to La Paloma, Uruguay. Information about this species is scarce. The relative growth of A. cribrarius was analyzed, based on some morphometric relations, where the carapace width, excluding lateral spines (CW), was used as an independent variable. A total of 403 specimens (189 males and 214 females), was collected in Ubatuba, State of São Paulo, Brazil, with otter-trawls. The animals were sexed and sorted to maturation phase (juvenile or adult). Some measurements were made: carapace (length and width excluding lateral spines), abdomen (greatest width of the fifth somite in females and the sixth in males) and major chela (greatest length, width and height, dactylus length). This study was made by the application of the power function (y=a.x(b)) which was fitted to the data and the pattern of growth established for each parameter by the ''b''-value (constant of allometry), as positive allometry (b>1), negative allometry (b<1) or isometry (b=1). The morphometric relations of the carapace showed a tendency to isometry. In females, the abdominal width grew in positive allometry, higher in juveniles (b=1.33) than in adults (b=1.18). In this case, an overlap and discontinuity was noticed between the phases over a carapace width range of 55 to 70 mm, where the puberty molt occurs. The majority of relationships showed that the major chela of the males grew in positive allometry, however, the greatest allometric difference between the phases was observed towards the propodus length with 1.09 as juvenile and 1.26 as adult ''b''values. In the males, this variable showed an inflection between the CW range of 45' to 55 mm, where the transition to the maturation phase occurs. The relative growth of this species is similar to those of previously studied species. This indicates, that the propodus length and the abdominal width are the morphometric variables most appropriate to estimate the size of the beginning of the sexual maturity for males and females of this species, respectively.